Studies on guest/host complexes, liposomal and other systems for potential chemotherapeutic drug(s) delivery - Fahmy, Sherif Ashraf (AUC Knowledge Fountain, 2020)
Following the discovery of cisplatin over 50 years ago, this platinum-based drug (PBD) has been a widely used and effective form of cancer therapy, primarily causing cell death by inducing DNA damage and triggering apoptosis. However, the dose limiting toxicity of cisplatin has led to the development of the newer generations' platinum-based drugs (second and third) that maintain the cytotoxicity of cisplatin but have more acceptable side-effect profiles. In addition to the creation of new analogs, tumor delivery systems such as liposome-encapsulated platinum drugs have been designed and are currently in clinical trials. In this study, we have created and characterized the first PEGylated liposomal form of the second generation PBD, nedaplatin (ND), using thin-film hydration. Nedaplatin, the main focus of this study, has been exclusively used in Japan for the treatment of esophageal, head, and neck, bladder, non-small cell lung cancer (NSCLC), ovarian, and cervical cancer. Here, we study the genotoxic and cytotoxic effects of free and liposomal nedaplatin on the human NSCLC cell line (A549) and human bone cancer cell line U2OS. We use a variety of assays, including the highly sensitive histone H2AX assay, to assess drug internalization and to quantify DNA damage induction. We show that by encapsulating nedaplatin in PEGylated liposomes, the cytotoxicity and genotoxicity of nedaplatin were significantly enhanced in both cell lines demonstrating the superior cell delivery potential of this product. The obtained promising results have led us to encapsulate the same drug in macromolecules, another drug delivery vehicle. Supramolecules, including macrocyclic candidates, can encapsulate various therapeutically active compounds via the formation of host-guest complexes to augment their water-solubility, and hence, bioavailability and improve stability. We present the first study, conducted experimentally and theoretically, of the complexation between p-4 sulfocalix[4]arene, a supramolecule possessing a bipolar amphiphilic nature and nedaplatin. The host molecule, p-4 sulfocalix[4]arene, possesses excellent biocompatibility and minimum toxic effects on red blood cells making it the perfect candidate in drug delivery. The formation of a 1:1 host/guest complex between p-4 sulfocalix[4]arene and nedaplatin was revealed from the data obtained from 1H NMR, UV, Job's plot analysis, HPLC and DFT calculations. The complex’s stability constant is calculated experimentally and found to be 3.6 × 104 M−1 and 2.1 × 104 M−1, which correspond to values of −6.2 and −5.9 kcal mol−1, respectively, for the complexation free energy. Also, the interaction free energy is estimated and found to be −4.9 kcal mol−1. The stability of the complex in solution is attributed to the formation of hydrogen bonds between the host and the guest. The cytotoxic activity of the formed complex was evaluated against MDA-MB-231 cells, and it exhibited enhanced antitumor activity compared to the free drug. These findings suggest that this complex could be used as a promising system in cancer therapy. Afterward, we formulated a more modern and controlled delivery system, which is triggered to release its cargo by the effect of local hyperthermia applied on the tumor site. In this aspect, we designed the first thermosensitive liposomes encapsulating ND and SC4-ND complex, ND-TSL, and ND-CX TSL, respectively. The outstanding physicochemical properties and EE of both systems, in addition to the excellent control over the release of the drug(s) at specific temperatures, have led us to encapsulate picoplatin, oral platinum-based drug, in TSLs forming P-TSL and the results were auspicious.